Penggunaan Media Kartu Berbahasa Indonesia-Mandarin Terhadap Pemahaman Materi Biologi Siswa Bilingual Di Pontianak - Reni Marlina; Yokhebed Yokhebed; Lily Thamrin (Universitas Sebelas Maret, 2018)
Instructional media in the learning process not only as a tool but a messenger or learning information that must be in accordance with the student needs. In this study, researchers developed a media that integrates biology learning with Mandarin so that when students learn biology, also simultaneously recognize objects in biology and organizational level of life in Mandarin. Instructional media that will be made in the cards form contains about the object and scope of biology. The purpose of this study is to measure the effectiveness of Indonesian-mandarin biology card on biology learning outcomes for secondary school. The method used is one shot case study. Research is done through the preparation, implementation, and data analysis. The results of the use media of Indonesian-mandarin card seen based on the average value of learning outcomes obtained test of 76.29% with mastery learning is in good criteria. Thus it can be concluded that the use of Indonesian-mandarin card can be one strategy to improve student learning outcomes in biology learning.